2015
DOI: 10.1007/s11999-014-4102-z
|View full text |Cite
|
Sign up to set email alerts
|

Does Patient Sex Affect the Rate of Mortality and Complications After Spine Surgery? A Systematic Review

Abstract: Background Available studies disagree regarding the influence of patient sex on mortality and complications after spine surgery. We sought to conduct a systematic review and pool the results of existing research to better understand this issue. Questions/purposes We performed a systematic review to address two questions: (1) Does sex (male versus female) influence mortality after spine surgery? (2) Does sex impact the development of postoperative complications after spine surgery?Methods This systematic review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 59 publications
0
13
1
Order By: Relevance
“…Previous studies have identified age, sex, and certain comorbidities as risk factors that are most often associated with mortality during lumbar spine procedures. 4,23,28,33,34 Despite these reported risk factors, it is also recognized that mortality rates in lumbar spine surgeries are historically low overall, with one large-scale study estimating an overall mortality rate of 0.13% across all lumbar surgical patients in the United States between 2003 and 2012. 26 This same study identified older age, black race, male sex, liver disease, and congestive heart failure to be significantly associated with increased mortality rates.…”
Section: Mortalitymentioning
confidence: 99%
“…Previous studies have identified age, sex, and certain comorbidities as risk factors that are most often associated with mortality during lumbar spine procedures. 4,23,28,33,34 Despite these reported risk factors, it is also recognized that mortality rates in lumbar spine surgeries are historically low overall, with one large-scale study estimating an overall mortality rate of 0.13% across all lumbar surgical patients in the United States between 2003 and 2012. 26 This same study identified older age, black race, male sex, liver disease, and congestive heart failure to be significantly associated with increased mortality rates.…”
Section: Mortalitymentioning
confidence: 99%
“…Patient variables such as age, sex, and the number and type of medical comorbidities have been found to influence the risk of complications that include deep wound infection, cardiopulmonary complication, thromboembolic disease, pulmonary embolism, cerebrovascular accident, and neurological deficit. 12,23,28,29,36,37,39 The types of medical comorbidities that the RAT incorporates are diverse, ranging from cardiac dysfunction to psychiatric disorders. Psychiatric disorders are well established in the spine population, considering the high rate of depression in patients with back pain.…”
Section: Risk Assessment Toolmentioning
confidence: 99%
“…The sex of a patient has previously been shown to have an impact on the outcome of a surgical intervention. [1][2][3][4][5][6][7][8][9][10] Women undergoing vascular surgery have been found to have higher mortality rates, more wound complications, greater need for blood transfusion, and increased length of stay. [1][2][3][4][5] In trauma surgery, male sex has been associated with increased mortality, length of stay, and complications.…”
Section: Introductionmentioning
confidence: 99%